KUALITAS NUTRISI PAKAN LOKAL YANG DISUPLEMENTASI ZN BIOKOMPLEK DAN VITAMIN E - Tintin Rostini; Irwan Zakir; Arief Hidayatullah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
The nutritional quality of local food in the poor Kalimantan region will be lacking in minerals because the place for growing forage plants in a land with margins (acid) makes the quality of mineral poor food ingredients. The purpose of this study was to determine the nutritional quality of local feed supplemented with biocomplex ZN and Vitamin E. The treatment in this study used a complete design (CRD) with 4 processing repetitions made from 16 experimental units, consisting of (Tl) local forage-concentrates l2% PK without Zn and vitamin E supplementation, (T 2) Tl-supplementation + 60 mg Zn / kg as biocomplex Zn and vitamin E (T3) Tl + l20 mg Zn / kg such as Zn biocomplex + vitamin E and (T4) Tl + l80 mg Zn Biokomplek / kg + vitamin E. Parameters collected are the nutritional quality and digestibility of dry matter and feed organic matter. The results shown from studies using biocomplex ZN up to 180mg / kg of feed (PT3) can increase the protein content and dry matter content of local feed, and can increase the digestibility of local dry matter and organic feed ingredients. It was concluded that ZN Biokomplek and Vitamin E can improve the quality of local feed.